Funkcja mitu politycznego w koncepcjach Alfreda Rosenberga - Wielomski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
This article is a reflection on the function of myth in the political theory of Nazism. Principal Nazi ideologue Alfred Rosenberg is the author of famous book "The Myth of the Twentieth Century" (1930). What is the role of myth in his concept? Why wasn’t it titled "The Ideology of Twentieth Century"? In my opinion, myth has two main roles in Rosenberg’s theory. Firstly, it’s great proposition of meaning of history and its enemies counters the Marxist ideology of history as a grand process of emancipation concluding with the proletarian revolution. As Marx and Marxists speak about history from the point of view of class struggles, Rosenberg speaks from the point of racial struggles. The second aim stems from what Rosenberg perceived as a absence of an idea of nation-state in Germany. For Rosenberg, the Germans from many countries and states do not have the common consciousness inherent in (and imperative for) a national community. In such circumstances the Nazis must themselves create a myth of a common German race as an objective and scientific “fact.” In the political ideas of Rosenberg, the Nordic race is the substitute of a normal nation and the idea of a nation-state
Keywords: Rosenberg, Alfred (1893–1946); nazizm; narodowy socjalizm; mit; rasa